Integral Assessment of the Development of Russia’s Chemical Industry - BURENINA, Irina; EVTUSHENKO, Evgeniy; KOTOV, Dmitry; BATTALOVA, Alena; GAIFULLINA, Marina; GAMILOVA, Dilyara (Journal of Environmental Management and Tourism; Vol 8 No 5 (2017): JEMT Volume VIII Issue 5(21) Fall 2017DO - 10.14505//jemt.v8.5(21).11, 2018)
In the context of global economic instability and great significance of the chemical industry, the chemical industry efficiency assessment is one of the key areas of research on economic branches. Scope of the research: indicators and growth drivers of Russia’s chemical industry. Methods used: logical analysis, grouping and comparison, generalization, and system approach. Using the method of factor analysis, the authors proposed the integral indicator of the chemical industry development. The article presents key indicators of Russia’s chemical industry development. The authors propose the integral approach to its assessing. Application of the proposed approach showed that for 2015 one can register a medium level of Russia’s chemical industry development. At the same time, the impact of environmental factors on its development is also evaluated as average. The article outlines the challenges and obstacles to Russia’s chemical industry development. The authors identify the priority areas of its development, considering the global structure of demand for chemical products.